Experience capitalization: Working towards its institutionalization - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
The cases captured in this booklet show the steps taken in many of these projects and organisations to support and ensure the adoption of an experience capitalization approach. Working together with their colleagues, those who joined the CTA workshops have become active “champions”: organising their own training sessions, they shared information in different ways, and have shown how others can benefit from the capitalization process. They have helped to create the conditions for experience capitalization to be more widely adopted by their organisations. As a result, there are many new capitalization processes going on, and many more will be taking place in the future – effectively underpinning more accountable and efficient projects in the future and greater progress in rural development.